Hearing the humanities: sonifying Steele’s Shakespeare - Emsley, Iain; Chamberlain, Alan; De Roure, David (2017)
We present initial work that explores the use of sonification to represent Joshua Steele’s symbolic notation. This provides a manner of overhearing a previous performance and testing the method’s reproducibility and uncertainties within it.